Quantification and phenotypic characterization of peripheral blood Vδ1 + T cells in chronic lymphocytic leukemia and monoclonal B cell lymphocytosis. Issue 2 (17th October 2018) - Simões, Catarina; Silva, Isabel; Carvalho, Anabela; Silva, Sandra; Santos, Susana; Marques, Gilberto; Ribeiro, André; Roque, Adriana; Carda, José; Sarmento‐Ribeiro, A.B.; Domingues, Maria do Rosário; Ribeiro, Letícia; et al.
Abstract : Background: Vδ1 + T cells, a subset of γδ T cells, are responsible for innate‐like immune responses. Recently, an anti‐tumor function mediated by MHC‐unrestricted recognition of lipid and stress molecules, has also been described in these cells. This study aimed to quantify and phenotypically characterize circulating Vδ1 + T cells in B cell Chronic Lymphocytic Leukemia (CLL) and Monoclonal B cell lymphocytosis (MBL). Methods: This study enrolled 58 individuals distributed in five groups: Binet B and C CLL ( n  = 9), Binet A CLL ( n  = 26), High count‐MBL ( n  = 10), Low count‐MBL ( n  = 5), and a control group ( n  = 8). The phenotypic characterization of Vδ1 + T cells, as well as the other T cell subpopulations (CD4 +, CD8 +, CD4 + /CD8 +, and Vδ1 − γδT cells), were assessed by flow cytometry, evaluating the frequency of each subset expressing CD27, CD69, and cytoplasmic granzyme B. Results: We observed an increasing percentage of Vδ1 + T cells belonging to CD27 − compartment from controls to advanced stages of the disease, which was accompanied by an increasing percentage of these cells expressing granzyme B, a phenotypic pattern that was also observed in the other T cell subpopulations under study since earlier stages of the disease. Moreover, a striking expansion of Vδ1 + T cells in Binet B and C CLL was observed. Conclusions: These experiment findings point to an expansion of CD27 ‐ Vδ1 + T cells with a cytotoxic profile, from controls to advanced stages of the disease, which points to a role of Vδ1 + T cells in the host's anti‐tumor responses against clonal B‐cells in MBL and CLL. © 2018 Clinical Cytometry Society